Microbiota Comparison of Amur ide (Leuciscus waleckii) Intestine and Waters at Alkaline Water and Freshwater as the Living Environment - Luo, Liang; Xu, Yue; Chang, Yumei; Sun, Bo; Zhang, Limin; Zhao, Zhigang; Liang, Liqun (Frontiers in Microbiology, 2022)
The gut microbiota differences should be investigated to explore the relationship between alkaline water and freshwater species (AW and FW, respectively) of Leuciscus waleckii in these different aquatic environments. In this study, we screened intestinal indicator flora and functional redundancy of intestinal colonies in AW and FW. The available versus community composition correlations were then predicted by contrasting each other with the flora contained in environmental water samples. Here, five microbial species and six genera were identified owing to the classifiable sequence. The intestinal microbiota that existed in AW and FW had approximately 1/3 of the operational taxonomic units (OTUs) in the respective living water environments, meaning that gut microbes in the aqueous habitats will have an influential association with gut microbes in AW and FW. Compared to the bacterial composition of FW intestine and that present in freshwater, Moraxella osloensis, Psychrobacter maritimus, and Psychrobacter faecalis were significantly enriched in the intestine of AW and in alkaline water samples. In the FW intestine and freshwater samples, however, Cryptomonas curvata, and Polynucleobacter asymbioticus were highly enriched, which can be summarized as Enterobacter sp. being the predominant population in the AW gut, while Aeromonas and Ralstonia being primarily present in FW intestines. Photosynthetic bacteria were most significant in both water samples. The results indicated that the intestinal microbiota composition, abundance, and diversity of AW and FW were quite different. Contrastly, the microbial composition of the additional alkaline water and freshwater environments showed slight differences. This study expects to enhance our understanding of the alkalinity tolerance of L. waleckii, which will be provided for the breeding of fish living in alkaline water, and push the development of alkaline water resources with increased efficiency.